Standardization and classification of events in tourism based on a systems approach - Golob, Aleksandra; Jere Jakulin, Tadeja (The European Journal of Applied Economics, 2014)
In this article we wanted to present the importance of event tourism for a destination and categorization of events considering the quality of organization, the quality of staff working on the event, the quality of the event program and the quality of event services. Our theoretical contribution to science is presented by the systems approach method which provides a clear overview of the researched topics and adequate support to decision making. The systems approach method is aimed at understanding the problem and finding an optimal solution. Our intention is to achieve the desired results and positive changes in the field of event tourism using the theory of systems. Within the systems approach method, we also used qualitative modeling of the CLD model of legislative system of events and investments in the events. We have presented our suggestions for achieving these elements through quality standards and classification of events, which leads to optimal categorization of events. Events take place every day, throughout the year, in and out of season, and their number increases each year. This is the main reason for giving more attention to the development of event tourism in the future. High quality events can distinguish us from other destinations and provide a clear advantage over the competition.
Keywords: the categorization and specialization of event; the legislative system of events; CLD model; system approach; modeling; the quality of event; the standardization and classification of the event; tourism; standard